STUDENTS' PERSPECTIVE ON PREREQUISITE SUBJECTS TOWARD THEIR THESIS WRITING - Ana Ahsana El-Sulukiyyah; Diah Anita Pusparini (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
This study investigates the students’ perspective on the prerequisite subjects toward their thesis writing. Some problems occurred when students doing their thesis. Those problems could be from their preparation and their comprehension of the prerequisite subjects. It is a descriptive qualitative study with open-ended questionnaire as the primary instruments to get the data. The subjects of this study were 31 students who were finishing their thesis. Results show that students are aware that prerequisite subjects are important to write their thesis, moreover the subject namely Thesis Writing Methodology. According to students’ opinion it was the prominent subject to know how to prepare and compose their thesis writing. The conclusion of this study is the prerequisite subject is important to prepare and help students finishing their thesis without any writing block.